PERSEPSI WISATAWAN PADA DAYA TARIK LOMBA PERAHU LAYAR DARWIN-AMBON DI NEGERI AMAHUSU KOTA AMBON - Hilary Nadia Jesajas; Lilian Matilda Soukotta; Renoldy Lamberty Papilaya (Universitas Pattimura, 2020)
Darwin-Ambon Yacht Race is an important annual tourism event conducted in collaboration with the Twin Cities (Sister City) between the governments of Ambon City (Indonesia) and Darwin City (Australia). Increasing the attractiveness of Amahusu coastal tourism destination as the main location of the event must be seriously managed so that the race can be continuously carried out. Besides, local community participation also needs to be continuously improved. The purpose of this study was to analyze the perceptions of foreign tourists in the attractiveness of the Darwin-Ambon Yacht Race in Amahusu. A survey method was used in which primary and secondary data were collected. The sampling method for choosing Amahusu was purposive sampling, whereas respondents (tourists) were selected using accidental sampling method. Data were analyzed using descriptive qualitative and quantitative, namely Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of Customer Satisfaction Index (CSI) calculation showed that although overall tourists were very satisfied (80.80%) of the Darwin-Ambon Yacht Race competition, but the cleanliness attributes of the coastal and marine areas (cleanliness area) were not fulfilled the tourist’s expectation because not optimally managed.